FINANCIAL LITERACY AND SAVING HABITS OF NIGERIAN UNIVERSITY STUDENTS (A Study Of Crawford University) - Adu Cecilia Adurayemi; Ejiks Oluwakemi Lateefat (Universitas Islam Negeri (UIN) Sumatera Utara, 2026)
The study evaluated the effect of financial literacy on the saving habits of Nigerian university students while the specific objective assessed the relationship between basic financial knowledge and the frequency of saving. Primary data were sourced from administration of well- structured questionnaire while regression analysis was adopted to analyze the data obtained. It was revealed that there was a significant effect of financial literacy on frequency of savings of students at (